De « Todo bajo el sol» à « España es parte de ti » : 30 ans de spots de promotion touristique - Ivanne Galant (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish State's interest in tourism and its action to promote it dates back to the beginning of the 20th century. The missions of the tourist institutions were the preservation of heritage, the development of the hotel and transport sectors and the promotion of tourism inside and outside the country. Since 1984, a centralising body –Inprotur (Instituto Nacional de Promoción del Turismo), renamed Turespaña in 1991– has been in charge of marketing. It has made it possible to develop a tourism promotion in line with the times and with new technologies. This article proposes to study the adverts produced by Inprotur and Turespaña since 1987 with the campaign "Everything under the sun" and 2017 with "Spain is part of you" in order to highlight their communication strategies (slogans, images and imaginaries mixed together). In addition, the study of these 30 years of videos will enable us to recreate a history of tourism in Spain, both from the point of view of supply and demand and see how these campaigns correspond to the logic of nation branding following little by little that of experiential marketing.